Stress and Sweet Food Craving Among University Students: A Cross-Sectional Correlational Study - Rava Zyaad; Adelina Rahmawati (Universitas Ahmad Dahlan, 2026)
Stress has been associated with maladaptive eating patterns, including an increased tendency to consume sweet foods. This study examined the relationship between perceived stress and sweet food craving among university students in Semarang, Indonesia. A cross-sectional correlational design was used, involving 228 students aged 18–23 years who completed an online questionnaire. Sweet food craving was assessed using a modified semi-quantitative food frequency questionnaire, while stress was measured using the stress subscale of the Depression Anxiety Stress Scales-21. The findings showed a small but significant positive association between stress and sweet food craving. Hierarchical regression analysis indicated that stress remained a significant predictor after gender was included in the model, although the explained variance was modest. Gender also contributed significantly, with female students reporting higher sweet food craving tendencies. However, exercise habits did not significantly predict sweet food craving. These findings suggest that stress may be related to students’ tendency to seek sweet foods, although the association is weak and should not be interpreted causally. The study contributes preliminary evidence on stress-related sweet food craving among Indonesian university students and highlights the need for future research using longitudinal designs and validated craving-specific measures.